(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to determine the effect of Brand Image and Brand Awareness on Brand Loyalty with Brand Trust as an Intervening Variable (Case Study of MS GLOW Product Users in Semarang City). The method used in this research is quantitative method, using primary data with data collection methods using a questionnaire. Hypothesis testing using the Structural Equation Model (SEM) method with the help of SmartPLS software. The results of this study prove that: (1) Brand Image has no effect on Brand Loyalty (2) Brand Awareness has a positive and significant effect on Brand Loyalty (3) Brand Image has a positive and significant effect on Brand Trust (4) Brand Awareness has a positive and significant effect on Brand Trust (5) Brand Image has a positive and significant effect on Brand Loyalty through Brand Trust as an intervening variable (6) Brand Awareness has a positive and significant effect on Brand Loyalty through Brand Trust as an intervening variable (7) Brand Trust has a positive and significant effect on Brand Loyalty.